Investigation of Direct Metal Laser Sintering Downskin Parameters’ Sagging Effect on Microchannels - Çalışkan, Cemal İrfan; Özer, Gökhan; Coşkun, Mert; Koç, Ebubekir (Springer, 2021)
Additive manufacturing technology is an innovative and advantageous production technology in producing microchannels, heat exchangers designed in complex geometries. Process parameters developed to provide production standardization and quality standards on production results are known. The study investigates the sagging effect of downskin parameters on the downfacing surfaces of microchannels designed in different geometries. In this context, the productions and SEM examinations and the geometric corrections obtained with the developed parameter sets are shared with tables and graphic studies. The direct metal laser sintering (DMLS) method was used in the parameter and production studies within the study’s scope.
Keywords: Conformal Cooling Channels; Additive Manufacturing; Direct Metal Laser Sintering; Process Parameters; Sagging